Analisis Tren Penelitian Pragmatik dalam Bahasa Kedua: Studi Bibliometrik dengan Vosviewer - Tara, Silmi Nur Azizah; Nindyaningrum, Fitria Wiyarti; Cahyani, Putri Ayu (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explore research trends in pragmatics within second language learning using a bibliometric approach. The data consists of 57 articles related to writing skills in literature, sourced from the Scopus database between 2020 and 2025, analyzed using VOSviewer software. The analysis reveals that the dominant topics are pragmatic competence and its development, with a particular focus on adult learners. Additionally, aspects such as pragmatic awareness, pragmatic production, and pragmatic transfer were found to be crucial in second language communication. The study also highlights the importance of technology and digital-based learning methods in supporting pragmatic teaching, which has become increasingly relevant in our interconnected world. The findings are expected to provide valuable insights into developing more practical and applicable methods for teaching pragmatics, helping second language learners effectively acquire pragmatic competence in a way that meets the demands of today’s globalized environment.